The Effect of Bait and Operating Time on the Catch of Basic Longline in Bantar Village, Rangsang Barat District, Kepulauan Meranti Regency - Hidayat, Syahyan Fitra; Brown, Arthur; Isnaniah, Isnaniah (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2023)
This research was conducted in Bantar village, Rangsang Barat subdistrict, Kepulauan Meranti regency, Riau Regency for 10 days on January 2021. This study aims to find out and analyze the effect of bait type and operating time (night and day) on the catch and the hook rate of the catch of fishing gear (bottom long line). The method used in this study is an experimental fishing method a method that can be done if the data to be obtained is not yet available so that the variables to be measured must be generated data through experiments, observation of the data can only be carried out after the experiment. With a complete random block design of a factorial pattern of 2 x 3 with a replay of 10 to be carried out on different days, which is then made into a block (group). The use of different types of bait (Bombay duck, sea worms, and flatfish) statistically has a noticeable effect on the number of fish catches on bottom fishing gear. The number of catches of longline fishing gear using Bombay duck bait got 74 catches with an average hook rate of 0.37% during the day and night operations, sea worm baits got 65 catches with an average hook value rate of 0.325% during the operating time during the day and at night, fish next door get 81 catches with an average hook rate of 0.405%.